The Use of Educational Applications by Children with Autistic Spectrum Disorder - A Case of Study - Magaton, Heloise Cristini Magaton; Bim, Silvia Amélia Bim; Keywords, Author Keywords (Teste, 2018)
Researchs on digital accessibility for people with cognitive disabilities is still incipient. Seeking to contribute changing this scenario, this article presents a study case on the use of eight different educational mobile applications by six children with Autistic Spectrum Disorder (ASD). The results indicate that software specifically developed or not for people with ASD can attend the needs of professionals that work with ASD children. The use of sounds, the accompaniment of experts during the use and the purpose of the use are factors that influence the satisfaction of the children using educational applications.